Association of GSTM1 and GSTT1 Polymorphism with Lipid Peroxidation in Benign Prostate Hyperplasia and Prostate Cancer: A Pilot Study. Issue 4 (28th May 2013) - Kumar, Vivek; Yadav, Chandra Shekhar; Datta, Sudip Kumar; Singh, Satyender; Ahmed, Rafat S.; Goel, Sanjay; Gupta, Sanjay; Mustafa, Md.; Grover, Rajesh Kumar; Banerjee, Basu Dev
Abstract : Association of glutathione S-transferase (GST) M1 and T1 deletions with benign prostate hyperplasia (BPH) and prostate cancer is well reported. These enzymes metabolize numerous toxins thus protecting from oxidative injury. Oxidative stress has been associated with development of BPH and prostate cancer. The present study was designed to analyze role of GST deletions in development of oxidative stress in these subjects. GSTs are responsible for metabolism of toxins present in tobacco therefore effect of tobacco usage in study groups was also studied. Three groups of subjects: BPH (57 patients), prostate cancer (53 patients) and controls (46 subjects) were recruited. Genotyping was done using a multiplex polymerase chain reaction (PCR) method. Malondialdehyde (MDA) levels as marker of oxidative stress were estimated by measuring thiobarbituric acid reactive substance (TBARS) in plasma. Based on genotyping, subjects were categorized into: GSTM1+/GSTT1+, GSTM1-/GSTT1+, GSTM1+/GSTT1- and GSTM1-/GSTT1- . Significantly higher plasma MDA levels were noticed in GSTM1-/GSTT1 - as compared to GSTM1+/GSTT1+ in all study groups. Double deletion ( GSTM1-/GSTT1- ) is associated with higher oxidative stress which might play a role in the pathogenesis of BPH and prostate cancer. However, other markers of oxidative stress should be analyzed before any firm conclusion. Erratum to "Association of GSTM1 and GSTT1 Polymorphism with Lipid Peroxidation in Benign Prostate Hyperplasia and Prostate Cancer: A Pilot Study" dx.doi.org/10.3233/DMA-2012-0929